Modelling large-scale evacuation of music festivals. (May 2016) - Ronchi, E.; Uriz, F. Nieto; Criel, X.; Reilly, P.
Highlights: Modelling is suggested to study large-scale evacuation at music festivals. A model case study has been simulated with an evacuation model. Simulated people-evacuation time curves helps identifying critical factors. Abstract: This paper explores the use of multi-agent continuous evacuation modelling for representing large-scale evacuation scenarios at music festivals. A 65, 000 people capacity music festival area was simulated using the model Pathfinder. Three evacuation scenarios were developed in order to explore the capabilities of evacuation modelling during such incidents, namely (1) a preventive evacuation of a section of the festival area containing approximately 15, 000 people due to a fire breaking out on a ship, (2) an escalating scenario involving the total evacuation of the entire festival area (65, 000 people) due to a bomb threat, and (3) a cascading scenario involving the total evacuation of the entire festival area (65, 000 people) due to the threat of an explosion caused by a ship engine overheating. This study suggests that the analysis of the people-evacuation time curves produced by evacuation models, coupled with a visual analysis of the simulated evacuation scenarios, allows for the identification of the main factors affecting the evacuation process (e.g., delay times, overcrowding at exits in relation to exit widths, etc.) and potential measures that could improve safety.